MEMAHAMI URGENSI PERBEDAAN MAZHAB DALAM KONSTRUKSI HUKUM ISLAM DI ERA MILLENIAL - Ikwanuddin Harahap (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2019)
Islam did not divided in the teachings of the school (mazhab) at first rising. After the death of the Prophet Muhammad, in carrying out Islamic Shari'a, especially at the level of fiqh, Muslims disorganized have followed the opinions of certain figures. This tradition has existed since sahabah era. The existence and dependence on the school from the beginning was a debate between the ulama. Mainstream leads to two groups, the first group that forbids following the school and the second is a group that allows schooling especially for lay people. In the millennial era marked by the complexity of the problems of Islamic law, the presence of mazhab was felt to be urgent. Mazhab provides an alternative solution to the problems of the contemporary people. The problems of Islamic law in the millennial era are increasingly diverse and complex both in terms of quality and quantity. The scholars are required to solve these problems by using various scientific disciplines to produce the right legal solutions. The presence of various schools has made an important contribution because it provides an alternative legal thinking that can be adopted at this time. The ability to contextualize legal thinking in the school to the present context is an important step to be taken.